Development of Creative Abilities of Preschool Children through Didactic Games - Dilshoda Atabaeva (Research Parks Publishers, 2022)
This article discusses the effectiveness of didactic games with theoretical representations in the development of preschool children's creative abilities, as well as their low-level diagnosis and psychology.